Prevalence and concordance in the prediction of excess body weight by two anthropometric criteria in adolescents of western Brazilian Amazon - Edson dos Santos Farias; Ivanice Fernandes Barcellos Gemelli; Orivaldo Florêncio Souza; Wagner de Jesus Pinto; Josivana Pontes dos Santos; Edio Luiz Petroski; Gil Guerra-Júnior (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to identify the prevalence and concordance of excess weight (BMI) and body fat (fat %) in adolescents of both sexes from cities of Rio Branco-AC and Porto Velho-RO. This study evaluated 4,310 adolescents, 2,167 from Rio Branco and 2,143 from Porto Velho. No difference (p=0.46) for excess weight between adolescents from Rio Branco (34.8%) and Porto Velho (33.8%) was observed. Fat percentage was significantly higher (p<0.01) in adolescents from Porto Velho (59.8%) compared to those from Rio Branco (44.3%). In intra-pubertal and pubertal stages, moderate concordance was identified (p<0.01) and in pre-pubertal stage, substantial concordance was observed (p<0.01). Thus, the findings of this study point out the adequacy of screening and diagnosis of obesity and overweight, which will enable earlier approach and treatment of adolescents.